Female Single Parenting: An Online Study about Self-Esteem and Parenting Styles of Brazilian Single Mothers - Rodrigues, Andressa da Silva (2024)
This is a quantitative study, with a descriptive and correlational design, whose objective was to investigate the relationship between self-esteem and parenting styles, taking Brazilian solo mothers as the target audience. The sample consisted of 41 women-mothers in a single-parent context, the majority from Ceará. The research was published on social networks and participants responded online to the Rosenberg Self-Esteem Scale, the Parenting Styles and Dimensions Questionnaire and the Sociodemographic Questionnaire. The results highlighted maternal overload, insufficient support network and the absence of the male father from the parental dynamics. Regarding parenting styles, the sample made greater use of the democratic style, however, the physical coercion dimension of the authoritarian style obtained a score higher than expected. Finally, the correlation test between the level of self-esteem and parental styles and dimensions indicated a positive and significant correlation only with the regulation dimension of the democratic style.